Keanekaragaman dan Manfaat Tanaman Obat Keluarga (TOGA) di Lingkungan Rumah Tangga - Parwito, Parwito; Effendi, Santoso Ujang; Khairani, Nurul (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2025)
This study examines the diversity and benefits of family medicinal plants (TOGA) in household settings, focusing on identifying the types of plants used and their health benefits. The research found 83 types of plants from 44 families commonly used as TOGA, including ginger, turmeric, and temulawak, which are known for their anti-inflammatory and antioxidant properties. Additionally, the study reveals that public knowledge about TOGA is relatively high, though further education is needed to optimize its use. The economic potential of herbal products derived from TOGA is also significant, indicating that cultivating TOGA not only benefits health but can also enhance family economic well-being. In conclusion, the utilization of TOGA has substantial potential to improve the overall quality of life and welfare of the community.